2010
DOI: 10.1038/hdy.2010.35
|View full text |Cite
|
Sign up to set email alerts
|

Population history and gene dispersal inferred from spatial genetic structure of a Central African timber tree, Distemonanthus benthamianus (Caesalpinioideae)

Abstract: African rainforests have undergone major distribution range shifts during the Quaternary, but few studies have investigated their impact on the genetic diversity of plant species and we lack knowledge on the extent of gene flow to predict how plant species can cope with such environmental changes. Analysis of the spatial genetic structure (SGS) of a species is an effective method to determine major directions of the demographic history of its populations and to estimate the extent of gene dispersal. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 49 publications
7
51
2
2
Order By: Relevance
“…In the GP located in South Cameroon and Gabon, wide-ranging LGM persistence of the species enabled rapid post-glacial recovery of population sizes, especially through pollen flow, and only an older bottleneck remained traceable. In this region, S. globulifera did not display SSR substructure, contrarily to other forest tree species (Born et al, 2011;Debout et al, 2011;Daïnou et al, 2010). Furthermore, our study suggested ecotypic differentiation between coastal or swamp forest and terra firme S. globulifera.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the GP located in South Cameroon and Gabon, wide-ranging LGM persistence of the species enabled rapid post-glacial recovery of population sizes, especially through pollen flow, and only an older bottleneck remained traceable. In this region, S. globulifera did not display SSR substructure, contrarily to other forest tree species (Born et al, 2011;Debout et al, 2011;Daïnou et al, 2010). Furthermore, our study suggested ecotypic differentiation between coastal or swamp forest and terra firme S. globulifera.…”
Section: Discussionmentioning
confidence: 67%
“…In Aucoumea klaineana, genetic diversity is structured in four differentiated gene pools (GPs; identified using nuclear microsatellites), the location of which coincides with refugia postulated from species distribution data in Gabon (Born et al, 2011). However, genetic patterns in three pioneer (Distemonanthus benthamianus, Erythrophleum suaveolens and Milicia excelsa) and one non-pioneer (Greenwayodendron suaveolens) species were not in agreement with postulated refuges but showed a common north-south divide in Lower Guinea, which was suggested to reflect the seasonal inversion near the equator (Daïnou et al, 2010;Dauby et al, 2010;Debout et al, 2011;Duminil et al, 2010). These emerging trends allow formulation of hypotheses on biogeographic scenarios and evolutionary processes operating within species that can be evaluated with multilocus genetic data (preferably using loci with contrasting inheritance) using statistical phylogeographic approaches (Knowles, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…The North-South divide nearby the Equator between these two clusters has been documented for other forest tree species (Duminil et al, 2010;Debout et al, 2011) and a significant floristic shift has recently been demonstrated at that latitude (Gonmadje, 2012). Cluster K5 centered on the Democratic Republic of the Congo may represent populations spreading from inland forest refuges surrounding the Congo River.…”
Section: Evolutionary History Of the Genus Miliciamentioning
confidence: 99%
“…First results show that some refugia were shared among several tree species with one main refugium in the North and one in the South of the thermal equator (e.g. Milicia excelsa in [53], Erythrophleum suaveolens in [55], Irvingia gabonensis in [56], Distemonanthus benthamianus in [60].…”
Section: Importance Of the Past Climatic Changes In Shaping Pattern Omentioning
confidence: 99%
“…Several phylogeographic studies using either cpDNA polymorphism [52,53,54,55,56,57] and/or nuclear markers such as RAPD [58] and microsatellite markers [53,59,60] have recently been published, considering Central African trees as model species, to give insight into the historical biogeography of the region. For most of the studied species, the genetic diversity is very spatially structured throughout the species distribution giving strong phylogeographic signals.…”
Section: Importance Of the Past Climatic Changes In Shaping Pattern Omentioning
confidence: 99%